STUDI KOMPARATIF INFEKSI ENDOPARASIT PADA SALURAN PENCERNAAN IKAN NILA MERAH (Oreocromis niloticus) DENGAN SISTEM BUDIDAYA YANG BERBEDA - Afriliyanti Harun; Yuniarti Koniyo; Arafik Lamadi; Mita Alvionita (Universitas Mataram, 2026)
Red tilapia (Oreochromis niloticus) is a freshwater commodity that is widely cultivated and has become one of the most popular fish for consumption among communities. Red tilapia is extensively farmed because it has several advantages, such as rapid growth, tolerance to both low and high temperatures, and euryhaline characteristics. In addition to these advantages, red tilapia farming also has weaknesses, one of which is parasitic infection. One of the causes of decreased productivity is parasite infection. Parasites are microorganisms that can infect many fish species; therefore, the researcher is interested in conducting this study to increase knowledge about the types of endoparasites, which is very important to facilitate handling when fish are infected by endoparasites. This research will be conducted for one month, and fish samples will be collected from different aquaculture systems. Parasite observations will be carried out at the Laboratory of the Fish Quarantine Station for Quality Control and Safety of Fishery Products (SKIPM) Class I Gorontalo. This study uses a descriptive method with a comparative approach. This research method is intended to describe every existing phenomenon, which may include forms, activities, characteristics, changes, relationships, similarities, and differences among phenomena (Rosita et al., 2023). When this method is combined with a comparative approach, the focus is on comparing two or more groups. Endoparasite examination will be conducted using the native method. The target organs examined include the digestive tract organs, namely the stomach and intestine